ORAL INTERPRETATION OF QS. AL-AHZAB:33 BY KH. SYA'RONI AHMAD: MAQASHIDI ANALYSIS - Rohmah, Miftahur (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
This paper discusses the oral interpretation of Kyai Sya'roni Ahmadi Kudus, who textually interpreted QS. Al-Ahzāb [33]:33. His interpretation is contrary to the current phenomenon, so the purpose of this paper is to find out the maqashid of Kyai Sya'roni's interpretation regarding the better women at home, and when they leave the house, there must be a companion or surveillance. This paper used descriptive analysis through the maqashidi Abdul Mustaqim interpretation approach. The results were obtained after applying the maqashidi interpretation method, including maslahah analysis, Qur'anic text and theme analysis, the historical context of revelation, the social context of Kyai Sa'roni in interpreting the al-Qur'an, and also social science analysis. By applying maqashid analysis, this paper argued that better women at home are a direction to preserve women's dignity. There are four alternative surveillance methods for women, e.g., close friends, security officers, constitution, and digital security system. The maqashid aspect of this verse is hifẓ al-nasl.